Green analysis of illicit drugs on banknote dust - Teresa Cecchi; Arianna Giuliani; Carlo Catini (Green Analytical Chemistry)
Purpose: This study aims to develop and validate the first analytical method to assess the presence of common illicit drugs on banknote dust from counting machines via green preanalytical and analytical approaches. Banknote dust represents the most eligible sample to ascertain the circulation of drugs of abuse. Prevalence measures of sociological interest, provided by analysing their traces on banknote dust, are less affected by the variability of their concentrations in each bill because banknote dust represents an averaged sample of high statistical significance. Methods: A simple banknote dust (10.0 ± 0.1 mg) extraction made use of 10 ml of a green extractant, comprising 98 % water, 2 % ethanol, and 0.1 % formic acid. A UHPLCHRMS system with ethanol as the organic modifier was used to develop and optimize the chromatographic method; a stable isotope labelled internal standard for each analyte was used to compensate matrix effects and possible losses. The Levene test, Mandel's test, and Shapiro-Wilk's test were used to obtain the best calibration model. The Green Analytical Procedure Index (GAPI), the Analytical GREEnness Metric Approach (AGREE), the and the Eco-scale were used to assess the greenness of the method. Results: Going green (AGREE score 0.83/1, Eco-Scale score 88/100) limits shortcomings due to the use of classical organic solvents in the extraction step and improves the chromatographic outcome. The linear weighted models gave limits of detections (LODs) ranging from 0.7 (3,4-Methylenedioxyamphetamine, MDA) to 3.9 ng/ml (Tetrahydrocannabinol, THC). For cocaine, they were lower than previously reported. For other analytes, no comparison can be provided because they were never analyzed in banknote dust. Intra-day and inter-day precision and accuracy were much better than those recommended by guidelines. The developed method was applied to 5 banknote dust samples from local banknote counter machines and 4 dust samples of different origins. No illicit drugs were found except cocaine in banknote dust. Its concentration ranged only one order of magnitude, from 2.76E+02 to 4.01E+03 mg of cocaine per gram of banknote dust, in agreement with previous results obtained with methanol as an extractant and organic modifier. Conclusions and perspectives: The greenness of the methods has many intrinsic merits for the environment, chromatographers and the chromatographic outcome. The way drug is consumed is more important than other ways of banknote contamination. To have an idea of drug circulation in a geographical area, the sampling of banknote dust can provide the police with reliable analytical evidence of high statistical value complementing results from anonymous questionnaires and drug seizures. Avoiding the processing of a large number of banknotes is an additional aim of Green Analytical Chemistry, since it entails waste prevention and an efficient use of resources.